THE IMPLEMENTATION OF USING FLASHCARDS TOWARDS STUDENTS PASSIVE VOICE MASTERY AT THE SECOND SEMESTER OF THE ELEVENTH CLASS OF SMA MUHAMMADIYAH 2 BANDAR LAMPUNG - LINA PURWATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
Many students at senior high school up to university found difficulties in learning English especially grammar. Grammar is one of English components that should be mastered by students who learn English because grammar is very valuable and important in using English. Grammar has many items and passive voice is one of grammar items which is very important and valuable to be learned. But in fact, most of graduate students of senior high school found difficulties to master passive voice well. Therefore, the teacher should pay attention to use the appropriate technique for teaching in the class. In this research, the researcher tried to investigate the use of